PENGARUH INFLASI DAN KURS TERHADAP HARGA SAHAM DI INDUSTRI DASAR DAN KIMIA - Efriyenty, Dian (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The higher the stock price, the financial condition of the company will look more stable and stronger, while when the stock price of a company decreases, the financial condition of the company will look unstable and weaker. The population taken from industrial and chemical manufacturing companies in the 2015-2019 period was 74 companies. The sample collection technique uses the purposive sampling method. The sample used in this study was 18 companies. The results of the study using the t test showed that partially inflation positively did not have a significant effect on stock prices while and exchange rates positively did have a significant effect on stock price.